Pemberdayaan UMKM desa melalui inovasi keripik Dangke: Varian rasa baru dan kemasan siap pasar - Mahyudin; Nur Fajrianti D; Sitti Aisyah Abdullah; Nur Fadilah; Ifa Nurasykin; Muh. Sofyan; Harianto; Aisyah; Farida; Andi Ahmad Saugi Suloengka (Jurnal Dedikasi Masyarakat, 2022)
This community engagement program aims to empower MSMEs in Dusun Pudukku, Pundi Lemo Village, Enrekang Regency through product innovation of dangke chips by developing new flavor variants and market-ready packaging. Dangke, a traditional local dairy product, has traditionally been sold in raw form with limited added value. Through a participatory approach, the program involved 15 MSME actors in technical training on dangke chip production with flavor variants including original, sweet-spicy, lime, and scallion, as well as packaging design using labeled PP standing pouches. Organoleptic testing by 50 local panelists showed that the sweet-spicy variant received the highest score in flavor and aroma. Packaging innovation also received a favorable response with an average score of 3.8, indicating improved consumer perception. This initiative increased partner income by 25% and facilitated a business transformation from raw to ready-to-eat products. The findings demonstrate that product and packaging innovations significantly enhance the competitiveness of local MSMEs.